Multiliteracy Enhancement Amid Pandemic: A Comprehensive Study on Pre-Service Science Teachers' Integration of Computer-Based Technologies - Gary Antonio Lirio; Antriman Orleans (Universidade Estadual de Alagoas, 2023)
The ongoing pandemic has significantly transformed the educational landscape, necessitating the design of curricula that seamlessly integrate innovative technologies and pedagogies to support students in a multimodal world. As a result, teacher-training programs must prioritize the development of pedagogical and technological skills for new educators. This investigation explored the utilization of computer-based technology (CBT) by pre-service teachers during classroom instruction and its integration for promoting multiliteracy in science education. The study connected CBT applications to Gardner's multiple intelligences theory and employed the Multiliteracy Pedagogy framework to analyze the technology used, adhering to the 7Es instructional model. Employing case study research and observation methodologies, the study assessed pre-service science teachers' demonstrations.The findings revealed that pre-service science teachers incorporated CBTs into their instruction, addressing various intelligences. Examples of CBTs included digital interactive whiteboards, virtual laboratories, video sharing websites, presentation software, and online quiz platforms. Although these tools accommodated diverse learners, the integration of CBTs into contextualized and localized approaches remained limited. Consequently, the results highlight the necessity for systematic strategies that enable pre-service teachers to effectively incorporate CBTs into various learning experiences. Such approaches facilitate a smooth transition from training to professional practice and promote the consistent use of technology at all levels of education